Ecological resilience and vegetation transition in the face of two successive large wildfires. (29th August 2021) - Steel, Zachary L.; Foster, Daniel; Coppoletta, Michelle; Lydersen, Jamie M.; Stephens, Scott L.; Paudel, Asha; Markwith, Scott H.; Merriam, Kyle; Collins, Brandon M.
Abstract: Wildfire can both promote and erode resilience to future disturbances in fire‐adapted ecosystems. Through a combination of past fire exclusion and climate change, fire patterns and successional trajectories are shifting with potentially negative consequences for forest resilience. In particular, high‐severity short‐interval reburns can lead to permanent transitions from forested to persistent non‐forested ecosystems. To test conditions under which wildfires promote resilience or initiate vegetation transitions we leveraged high‐resolution LiDAR data, field data and a natural experiment where two uncharacteristically severe wildfires burned the same area in California's Sierra Nevada mountains. Specifically, we evaluate what factors influence resistance to high‐severity reburn and whether early forest recovery is evident following vegetation transition. Our findings indicate that topography and vegetative structure influenced resistance to high‐severity effects of a second wildfire and that environmental heterogeneity played an important role. Forests that survived the initial burn were most resistant to subsequent high‐severity fire when they were characterized by relatively dense but heterogeneous upper strata and a sparse understorey, located in variable and mesic terrain and burned under milder fire weather conditions. Early seral vegetation was most likely to resist repeat high‐severity fire and potentially continue post‐fire forest recovery when it was located in variable and mesic terrain and was characterized by relatively sparse understorey vegetation and a heterogeneous subcanopy. Some early seral areas that reburned at lower severity showed signs of conifer forest recovery. Vegetation structure and composition of areas that repeatedly burned at high severity are consistent with a transition to persistent shrubland or hardwood forests. Synthesis . Short‐interval reburns close to historical fire intervals but of unusually high burn severity can create challenges for maintaining resilient forests, as sequential fires can expand upon and stabilize non‐forest vegetation. However, forest communities that survive such disturbances appear partially restored with increased structural heterogeneity and greater resistance to future high‐severity fire. If climate and fire regime trends continue, we are likely to see broadscale shifts towards vegetation types and species able to recover quickly from high‐severity fire at the expense of forests and species resistant to frequent low‐severity fire. Abstract : Short‐interval reburns close to historical fire intervals but of unusually high burn severity can create challenges for maintaining resilient forests, as sequential fires can expand upon and stabilize non‐forest vegetation. However, forest communities that survive such disturbances appear partially restored with increased structural heterogeneity and greater resistance to future high‐severity fire. If climate and fire regime trends continue, we are likely to see broadscale shifts towards vegetation types and species able to recover quickly from high‐severity fire at the expense of forests and species resistant to frequent low‐severity fire.